(untitled) (World Science, 2018)
Inflammatory diseases of the pelvic organs are characterized by the formation on the mucous membrane of the genital tract of multicomponent associations of conditionally pathogenic microflora. In order to evaluate the microbiocenosis of the genital tract during 2013-2017, 554 women with inflammatory diseases of the pelvic organs were examined. The task of the study included studying the frequency and structure of microbial associations that contaminated the genital tract of women with inflammatory diseases of the pelvic organs and analysis of vaginal microecology changes during 2013-2017. It is established that during the period from 2013 to 2017, in women with inflammatory diseases of the pelvic organs, an increase in the frequency of registration in the vaginal stems of the conditionally pathogenic microflora associations is observed. In the 2016 and 2017 dominant variants of associations of bacterial flora, the presence of S.epidermidis (heme +) and S. faecalis vagina was observed in the examined patients. The active proliferation of opportunistic microflora on the mucous membrane of the genital tract in patients with inflammatory diseases of the small pelvis was accompanied by a deficiency of lactobacilli and an increase in specific gravity in the associations of fungi of Candida.